Wire‐guided biliary cannulation technique does not reduce the risk of post‐ERCP pancreatitis: Multicenter randomized controlled trial. Issue 3 (19th September 2012) - Kobayashi, Go; Fujita, Naotaka; Imaizumi, Kazuomi; Irisawa, Atsushi; Suzuki, Masaki; Murakami, Akihiko; Oana, Shuhei; Makino, Naohiko; Komatsuda, Tomoya; Yoneyama, Kazuo
<x xml:space="preserve">Abstract</x> Aim To evaluate the effect of wire‐guided biliary cannulation (WGC) on the prevention of post‐endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP). Methods We investigated the impact of the WGC technique on the incidence of PEP by comparing the conventional cannulation (CC) technique in selective bile duct cannulation during ERCP with a cross‐over design in a prospective multicenter randomized controlled trial and the potential risk factors for PEP. This involved six tertiary referral centers and three university hospitals. A total of 322 patients with indications for ERCP requiring selective biliary cannulation were enrolled from April 2008 to March 2009. Results One hundred and sixty‐three patients were assigned to the WGC group and 159 to the CC group. The incidence of PEP was the same between the groups (6.1% vs 6.3%, P = 0.95). Primary successful biliary cannulation was achieved in 136 patients (83%) in the WGC group and in 138 (87%) in the CC group (P = 0.40). The mean time required for primary successful biliary cannulation was 7.4 ± 8.3 min and 7.2 ± 7.9 min, respectively (P = 0.83). Multivariate analysis demonstrated that accidental guidewire insertions and unintended injections of contrast into the main pancreatic duct were the only independent risk factors for PEP (P = 0.001, relative risk [RR]: 8.70, 95% confidence interval [CI]: 2.46–30.81). Conclusion The WGC technique does not reduce the risk of PEP and also does not improve the success rate of selective bile duct cannulation.